Antecedents to Customer Retention in a Corporate Context - Luciene Eberle; Gabriel Sperandio Milan; Celso Augusto de Matos (BBR: Brazilian Business Review)
Strategies for relational practice can vary considerably, depending on which constructs are driving customer retention. In this sense, we developed and tested a theoretical model considering the constructs: perceived value, service provider reputation, trust, and switching costs as antecedents to customer retention. This quantitative descriptive study began from a survey, which was applied to a sample of 269 companies-customers of a health plans operator. The data was analyzed with the use of a structural equation modeling. The results show that the perceived value influences on reputation; that reputation impacts on trust and switching costs; that switching costs are configured as antecedent to customer retention; and that customer retention is influenced by reputation. Finally, the moderating effect of customer time was investigated by means of the hierarchical regression, there being no statistically significant relationship between switching costs and customer retention.